The Validity of the Abbey Pain Scale for Assessing Pain in Stroke Patient - Arsyawina, Arsyawina; Parellangi, Parellangi; Widiastuti, Hesti Prawita; Hilda, Hilda (Universitas STRADA Indonesia, 2021)
Background: Apasia and dementia are two of the post-symptoms of stroke disease that cause patients to experience verbal communication disorders, thus requiring nurses to be more sensitive in assessing pain that is felt.Objective: The purpose of this research is to test the validity of the Abbey Pain Scale in assessing pain in stroke patients who are unable to express pain verbally.Methods: This research is a quantitative study using analytic observational research methods. This study used a consecutive sampling technique with the calculation of sample size based on population proportions. Research on one subject was repeated three times at rest and during pain procedures using the Abbey Pain Scale. Data were analyzed using the Pearson and Spearman test.Results: There was a significant correlation (p = 0.001) with a positive and strong correlation coefficient between the Abbey score and the pulse rate (correlation r = 0.699). Then there was a significant correlation (p < 0.001) with a positive and strong correlation coefficient between Abbey scores and mean arterial pressure (correlation r = 0.911). In addition, the Abbey Pain Scale score showed a significant change between the Abbey score at rest and during the pain procedure, both in the morning, afternoon and evening team nurses (p < 0.05).Conclusion: The Abbey Pain Scale is a valid measurement tool in assessing pain in stroke patients.